Computer Anxiety, Computer Self-Efficacy dan Perceived Usefulness oleh Pelaku UMKM - Rena Widiyasari; Bety Nur Achadiyah (Universitas Negeri Malang, 2019)
Abstract: This study aims to examine the interest of MSME owners in using accounting information technology with the influence of computer anxiety, computer self-efficacy, and perceived usefulness. This study used a quantitative research design and data collection techniques using the questionnaire method. The results showed that computer anxiety had a negative effect on the interest of MSMEs in applying accounting information technology, because of the high fear and low sense of anticipation would further reduce interest. Meanwhile, computer self-efficacy and perceived usefulness variables have a positive effect on the interest of MSME owners in applying accounting information technology. With these results, it is expected to increase the awareness of MSME owners to apply accounting information technology in their business.Abstrak: Penelitian ini menguji minat pelaku UMKM terhadap penggunaan teknologi informasi akuntansi dengan adanya pengaruh dari computer anxiety, computer self-efficacy, dan perceived usefulness. Penelitian ini menggunakan rancangan penelitian kuantitatif dan teknik pengumpulan data menggunakan metode kuisioner. Hasil penelitian menunjukkan bahwa computer anxiety berpengaruh negatif terhadap minat pelaku UMKM dalam menerapkan teknologi informasi akuntansi, karena tingginya rasa takut dan rendahnya rasa antisipasi akan semakin mengurangi minat. Sedangkan, variabel computer self-efficacy dan perceived usefulness berpengaruh positif terhadap minat pelaku UMKM dalam menerapkan teknologi informasi akuntansi. Dengan adanya hasil ini, diharapkan dapat meningkatkan kesadaran para pelaku UMKM untuk menerapkan teknologi informasi akuntansi dalam usahanya.